Malaysia's development challenges graduating from the middle - Hill, Hal 1948; Tham, Siew Yean; Ragayah Haji Mat Zin (Routledge Malaysian studies series, 2012)
"This book identifies and discusses the key aspects of Malaysia's current development policy challenges. Subjects covered include technology, education and skills, the promotion of entrpreneurship, social issues, monetary policy and governance issues, with the discussion of each subject empirically rich, rooted in Malaysia's development experience, and forward looking."--Publisher's description.